2019
DOI: 10.1093/jbcr/irz068
|View full text |Cite
|
Sign up to set email alerts
|

Weaning of Children With Burn Injury by Noninvasive Ventilation: A Clinical Experience

Abstract: The aim of this study was to report the respiratory management of a cohort of infants admitted to a Pediatric Intensive Care Unit (PICU) over a 7-year period due to severe burn injury and the potential benefits of noninvasive ventilation (NIV). A retrospective review of all pediatric patients admitted to PICU between 2009 and 2016 was conducted. From 2009 to 2016, 118 infants and children with burn injury were admitted to our institution (median age 16 months [IQR = 12.2–20]); 51.7% of them had face burns, 37.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…(2019) [11] Eligibility criteria for inclusion were as follows: severe blunt chest trauma, with an injury severity score (ISS) of >15, and a thorax abbreviated injury score (AIS) >3; pulmonary contusion of>10% of the total lung volume, documented by admission computed tomographic scan; need for tracheal intubation and mechanical ventilation for at least the first 48 h post trauma. Also, Piastra M et al (2019) [12] The effectiveness of NPPV was demonstrated by an improvement in the PaO2, an increase in the tidal volume and a decrease in the respiratory rate.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) [11] Eligibility criteria for inclusion were as follows: severe blunt chest trauma, with an injury severity score (ISS) of >15, and a thorax abbreviated injury score (AIS) >3; pulmonary contusion of>10% of the total lung volume, documented by admission computed tomographic scan; need for tracheal intubation and mechanical ventilation for at least the first 48 h post trauma. Also, Piastra M et al (2019) [12] The effectiveness of NPPV was demonstrated by an improvement in the PaO2, an increase in the tidal volume and a decrease in the respiratory rate.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In a recent study, prolonged mechanical ventilation significantly extended the length of intensive care and hospital stay for burn patients. 5,6 The leading causes were the weakness of the respiratory muscles, ventilator-related pneumonia, lung injury, and other related complications caused by prolonged mechanical ventilation. [7][8][9] Regarding prolonged mechanical ventilation, independent risk factors have been reported in many studies, including patients with various types of surgery 10,11 and critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical ventilation is still a life‐saving intervention for critically ill patients 3,4 . In a recent study, prolonged mechanical ventilation significantly extended the length of intensive care and hospital stay for burn patients 5,6 . The leading causes were the weakness of the respiratory muscles, ventilator‐related pneumonia, lung injury, and other related complications caused by prolonged mechanical ventilation 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 27% of the pediatric burn patients in the VPS database were diagnosed with acute respiratory distress syndrome, and 26% had two or more organ failures. Single-center retrospective studies in PICUs outside the United States also report high rates of IMV utilization, ranging from 21% to 37% of cases (5, 14). Unfortunately, these IMV utilization rates are not easily compared with the report by Garren et al (1), which drew from all acute burn admissions and not only their ICU admissions.…”
mentioning
confidence: 99%
“…Nearly 27% of the pediatric burn patients in the VPS database were diagnosed with acute respiratory distress syndrome, and 26% had two or more organ failures. Single-center retrospective studies in PICUs outside the United States also report high rates of IMV utilization, ranging from 21% to 37% of cases (5,14). Unfortunately, these IMV utilization rates are not easily compared with the report by Garren et al (1), which drew from all acute burn admissions and Although studies like the one by Garren et al (1) add to our understanding of pediatric burn intensive care, a more comprehensive look at children across the pediatric burn care multiverse is needed to fully understand IMV and other critical care resource utilization in this population.…”
mentioning
confidence: 99%